Implementing Industry 4.0 in SMEs Concepts, Examples and Applications - Matt, Dominik T.; Modrák, Vladimír; Zsifkovits, Helmut (Springer Nature, 2021)
This open access book addresses the practical challenges that Industry 4.0 presents for SMEs. While large companies are already responding to the changes resulting from the fourth industrial revolution , small businesses are in danger of falling behind due to the lack of examples, best practices and established methods and tools. Following on from the publication of the previous book 'Industry 4.0 for SMEs: Challenges, Opportunities and Requirements', the authors offer in this new book innovative results from research on smart manufacturing, smart logistics and managerial models for SMEs. Based on a large scale EU-funded research project involving seven academic institutions from three continents and a network of over fifty small and medium sized enterprises, the book reveals the methods and tools required to support the successful implementation of Industry 4.0 along with practical examples.